The Implementation Of Islamic Law In The Sale And Purchase Agreement Of The Rumbia Plantation In Riau-Lingga With The Code Eap153/10/2: A Philological Study Of A 20th Century Malay Manuscript - Aalaa Hilyati; Mamlahatun Buduroh (Insitut Muslim Cendekia, 2025)
This study examined the implementation of Islamic law in the Riau-Lingga rumbia plantation sale and purchase Agreement coded EAP153/10/2 which was stored in the Endangered Archives Programme (EAP) digital catalogue, British Library. This research showed the principles of Islamic law such as the pillars and conditions for valid sale and purchase, as well as the role of the judges and witnesses which were internalized in administrative documents during the Riau-Lingga Sultanate in the 20th century. The purpose of this study was to analyze the application of the law of sale and purchase based on an Islamic perspective through a study of philology and fiqh muamalah according to the Imam Syafi’i mazhab. The research used a descriptive-qualitative approach with philological methods to present texts and analysis of Islamic law to assess the validity of transactions according to Sharia. The results of the study showed that the letter had fulfilled the pillars and requirements of a valid sale and purchase, which can be seen through the presence of a contract, ijab kabul, identification of the seller and buyer, object and exchange value, and supporting validity by involving the role of the judge and witnesses. The novelty of this research lay in the integration of philological studies and Islamic law in analyzing historical documents in the scope of the old Malay manuscript treasury. The implications of this research strengthened the understanding that Islamic law had played a dominant role in the local Malay legal system in the past and could serve as a reference for legal policies based on local wisdom today.